Dampak Penyakit Tanaman terhadap Pendapatan Petani Kubis-kubisan di Daerah Agropolitan Kabupaten Cianjur, Jawa Barat - Teguh Pratama; Gede Suastika; Ali Nurmansyah (Jurnal Fitopatologi Indonesia, 2016)
Cruciferous vegetables are very important agricultural commodities for increasing  farmers  income. The main obstacles in their cultivation involved among others high level of pathogen infestation that may cause reduction in farmer’s income. This research was conducted to determine the main pathogens and their impact on farmer income in Agropolitan area of Cianjur Regency, West Java Province. The research was conducted through three activities, i.e. farmer survey, identification of the main pathogens, and measurement of disease intensity. The results showed that there were three main pathogens on assessed cruciferous vegetables, i.e. Alternaria brassiccicola (alternaria leaf spot), Plasmodiophora brassicae (clubroot), and Xanthomonas campestris (black rot), with disease intensity of 16.7%, 18.7%, and 15.1%, respectively. Clubroot disease was the most affecting disease in decreasing the  production of cruciferous vegetables and the farmer income. Incidence of clubroot disease with an average disease intensity of 16.67% might lead to the decrease of farming income about 24%–28%.